Making the developmental system work better for children: lessons learned implementing an innovative programme. Issue 3 (30th March 2012) - Branch, Sara; Homel, Ross; Freiberg, Kate
ABSTRACT Pathways to Prevention is an early prevention project founded on developmental systems theory operating through a schools‐community agency‐university partnership in a socially disadvantaged area of Brisbane. Circles of Care is a Pathways programme also implemented on a small scale by the same agency in a regional city. The Circles programme is designed to strengthen connections between schools, families and community services, and harmonize activities in these settings by surrounding children with identified needs with a supportive group of adults. A Circle, which includes at least the child, parent(s), teacher and agency staff, sets goals, mobilizes resources for the child, family and school, and monitors progress. The client is conceptualized not as the child but as a dysfunctional developmental system, with better outcomes for children as the ultimate goal. Qualitative evaluation at the two sites showed that while Circles worked well at the level of practical support and relationship building and did achieve good child outcomes, its capacity to achieve collaborative practice and strengthen system relations was limited by entrenched organizational structures and cultures. However, one site, with more support for collaboration across organizational boundaries, suggested that system alignment is achievable on a larger scale with vision and leadership for organizational reform.